2012
DOI: 10.1016/j.virol.2012.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Cis-acting element (SL1) of Potato virus X controls viral movement by interacting with the NbMPB2Cb and viral proteins

Abstract: A number of candidate tobacco proteins that bind to cis-acting elements (SL1 RNAs) of Potato virus X (PVX) have been identified in previous studies. We further characterized TMV-MP30 binding protein 2C (MPB2C) homologous protein. We isolated NbMPB2Cb from Nicotiana benthamiana and confirmed the interaction of NbMPB2Cb with SL1 RNAs in vitro. The mRNA level of NbMPB2Cb was increased upon infection by PVX and Tobacco mosaic virus. The movement of PVX was reduced by overexpression of NbMPB2Cb and increased by sil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 56 publications
0
20
0
Order By: Relevance
“…Another example is PMTV, whose TGB1 protein interacts with microtubules (Shemyakina et al, 2011;Wright et al, 2010) and thus may provide anchorage to support VRC formation at the ER. Microtubule association was also reported for the coat protein of PVX (Serazev et al, 2003) and the observation that PVX movement is inhibited by expression of a microtubule-associated protein seems to support a microtubule-associated movement mechanism (Cho et al, 2012). Grapevine fanleaf virus (GFLV) is a "tubule-forming" virus, which moves cell-to-cell in the form of encapsidated virions through tubules that are assembled by MP within the plasmodesmal pore.…”
Section: Cellular Mechanism Of Vrc Movementmentioning
confidence: 84%
“…Another example is PMTV, whose TGB1 protein interacts with microtubules (Shemyakina et al, 2011;Wright et al, 2010) and thus may provide anchorage to support VRC formation at the ER. Microtubule association was also reported for the coat protein of PVX (Serazev et al, 2003) and the observation that PVX movement is inhibited by expression of a microtubule-associated protein seems to support a microtubule-associated movement mechanism (Cho et al, 2012). Grapevine fanleaf virus (GFLV) is a "tubule-forming" virus, which moves cell-to-cell in the form of encapsidated virions through tubules that are assembled by MP within the plasmodesmal pore.…”
Section: Cellular Mechanism Of Vrc Movementmentioning
confidence: 84%
“…They observed that MPB2C is not essential for the movement of MP, but subcellular localization of MP clearly changed toward PDs. MPB2C also acts as a modulator for intercellular trafficking of PVX (Cho et al, 2012). …”
Section: Microtubule Associationmentioning
confidence: 99%
“…PVX is one of the most common plant viruses and causes great economic losses to solanaceous crops around the world [1]. This virus induces mild to no symptoms, but increased symptom expression has been observed in mixed infections with other plant viruses [11,47].…”
Section: Introductionmentioning
confidence: 99%